2022
DOI: 10.1093/ntr/ntac207
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Demographics, Dependence, and Biomarkers With Transitions in Tobacco Product Use in a Cohort of Cigarette Users and Dual Users of Cigarettes and E-cigarettes

Abstract: Introduction It is uncertain whether e-cigarettes facilitate smoking cessation in the real world. We aimed to understand whether and how transitions among cigarette, e-cigarette, and dual use are associated with sociodemographics, dependence measures, and biomarkers. Methods We followed 380 adult daily cigarette users and dual users every 2 months for up to 2 years. We estimated transition rates between non-current, cigarette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…To do so, we use continuous-time multistate transition models, which are increasingly being used to analyse tobacco product transitions and to understand how sociodemographic factors impact these underlying rates. [17][18][19][20][21][22][23][24] In a previous multistate transition analysis, we found that ENDS use in 2013-2017 was less persistent than cigarette use in the USA, 19 but more recent work has suggested that ENDS use has become more persistent in recent years. 15 In this analysis, we build on that previous work, implementing a multistate transition model using data from the Population Assessment of Tobacco and Health (PATH) Study, distinguishing between waves 2-4 (2015-2017) and waves 4 and 5 (2017-2019) for adults and youth, and adjusting for demographics and frequency of product use.…”
Section: Original Researchmentioning
confidence: 75%
See 1 more Smart Citation
“…To do so, we use continuous-time multistate transition models, which are increasingly being used to analyse tobacco product transitions and to understand how sociodemographic factors impact these underlying rates. [17][18][19][20][21][22][23][24] In a previous multistate transition analysis, we found that ENDS use in 2013-2017 was less persistent than cigarette use in the USA, 19 but more recent work has suggested that ENDS use has become more persistent in recent years. 15 In this analysis, we build on that previous work, implementing a multistate transition model using data from the Population Assessment of Tobacco and Health (PATH) Study, distinguishing between waves 2-4 (2015-2017) and waves 4 and 5 (2017-2019) for adults and youth, and adjusting for demographics and frequency of product use.…”
Section: Original Researchmentioning
confidence: 75%
“…Other limitations of the method include the lack of accounting for individuals' longer-term product trajectories (Markov assumption) and our inability to make causal inferences (eg, differences in cigarette initiation between those who never established use and those who use ENDS only may be caused by underlying demographic differences in the two populations, not the ENDS use itself). Additionally, while the model does account for the possibility of multiple transitions between follow-up points, yearly data (and, for adults in waves 4 and 5, every other year) are not sufficient to capture shorter-term transitions in past 30-day use 22 or the dynamics of experimentation with smoking or vaping. We also did not account for ENDS flavouring in this analysis.…”
Section: Original Researchmentioning
confidence: 99%
“…The benchmark results of this study are those of a specific machine learning model from the XGBoost, which is widely regarded as a cutting-edge machine learning model. It is possible that the model's performance can be improved and it may have underperformed in the previous study due to suboptimal hyperparameter tuning procedures [25][26][27]. This paper extracts sampling data features for different data sources in different situations, and selects a portion of data samples from the overall dataset for the process of model training research.…”
Section: Methodsmentioning
confidence: 99%
“…It is not subject to copyright under 17 USC 105 and is also made available preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. use multistate transition models, which are increasingly being used to analyze tobacco product transitions and to understand how sociodemographic factors impact these underlying rates [15][16][17][18][19]. In a previous multistate transition analysis, we found that ENDS use in 2013-2017 was less persistent than cigarette use in the US [15], but more recent work has suggested that ENDS use has become more persistent in recent years [20].…”
Section: Introductionmentioning
confidence: 91%